A CRITICAL REVIEW OF THE SINGAPORE ENGLISH LANGUAGE SYLLABUS AS AN ADVANCE SYLLABUS IN ENGLISH LANGUAGE TEACHING (ELT) - Imam Munandar (Jurnal As-Salam, 2020)
Abstract: The syllabus function as a framework that provide a national standard from which teachers gain a clear target of teaching English in schools. This research is a descriptive study by which it critically reviews the English language syllabus in Singapore, as an advance syllabus at time. The instrument of the review is a set of syllabus review outlined by Chew. This research has found th the at syllabus is seen to be organized around the functional approach which necessitates the language in use. Besides, it conceptualizes language as an integration of linguistics, sociocultural, discourse and strategic competences. Teaching and learning leaning language is heavily put on learning process. It sees language acquisition involves certain processes and strategies, and thus teacher should focus on them. The syllabus implementation faces some challenges. Some teachers have different belief and values from the syllabus and resist the adoption. While the syllabus prescribes the communicative approach, they retain structuralism and behaviorism in teaching and learning the language. This situation is worsened by some technical issues. Some heads of department in schools have weak socialization of the syllabus in their schools, leading it unnoticed by teachers. Some textbooks fail to comply with the approach prescribed in the syllabus and thus demand a larger effort from teachers to select textbooks that accurately reflect the syllabus. Keywords: Chew’s Critical Review of Syllabus, English language syllabus, English Language Teaching Abstrak: Fungsi silabus sebagai kerangka kerja yang menyediakan standar nasional supaya para guru mendapatkan target yang jelas untuk mengajar bahasa Inggris di sekolah. Penelitian ini adalah penelitian deskriptif yang mengkaji silabus bahasa Inggris secara kritis di Singapura, sebagai silabus lanjutan pada saat itu. Instrumen ulasan adalah seperangkat tinjauan silabus yang digariskan oleh Chew. Penelitian ini menemukan bahwa silabus diorganisir dengan pendekatan fungsional yang mengharuskan bagaimana bahasa digunakan. Selain itu, bahasa dikonsepkan sebagai integrasi linguistik, sosiokultural, wacana dan kompetensi strategis. Mengajar dan belajar bahasa sangat bergantung pada proses belajar. Hal ini terlihat dari penguasaan bahasa melibatkan proses dan strategi tertentu, dan dengan demikian guru harus fokus pada strategi tersebut. Sementara itu, implementasi silabus menghadapi beberapa tantangan. Beberapa guru memiliki kepercayaan dan nilai yang berbeda dari silabus dan menolak untuk di adopsi. Ketika silabus menentukan pendekatan komunikatif, mereka mempertahankan strukturalisme dan behaviorisme dalam mengajar dan belajar bahasa. Situasi ini diperburuk oleh beberapa masalah teknis. Beberapa kepala departemen di sekolah memiliki sosialisasi silabus yang lemah di sekolah mereka, sehingga tidak diperhatikan oleh guru. Beberapa buku teks gagal mematuhi pendekatan yang ditentukan dalam silabus dan karenanya menuntut upaya yang lebih besar dari guru untuk memilih buku teks yang secara akurat yang mencerminkan silabus. Kata Kunci: Analisa kritis silabus Chew, Silabus Bahasa Inggris, Pembelajaran Bahasa Inggris